Behavioral antecedents for handwashing in a low-income urban setting in Bangladesh: an exploratory study - Musarrat J. Rahman; Fosiul A. Nizame; Leanne Unicomb; Stephen P. Luby; Peter J. Winch (BMC, 2017)
Abstract Background Health programs commonly promote handwashing by drawing attention to potential fecal contamination in the environment. The underlying assumption is that the thought of fecal contamination will result in disgust, and motivate people to wash their hands with soap. However, this has not proven sufficient to achieve high rates of handwashing with soap at key times. We argue that handwashing with soap is influenced by broader range of antecedents, many unrelated to fecal contamination, that indicate to people when and where to wash their hands. This exploratory study aimed to identify and characterize this broader range of handwashing antecedents for use in future handwashing promotion efforts. Methods First, an initial list of behavioral antecedents was elicited through unstructured interviews, focus group discussions and observation with residents, from a low-income community in Dhaka, Bangladesh, who were also recipients of a handwashing intervention. Then, photographs representing three categories of behavioral antecedents were taken: activities of daily living, visual or tactile sensations, and handwashing-related hardware and activities. Finally, the research team conducted ranking exercises with a new set of participants, from the same area, to assess the perceived importance of each antecedent illustrated by the photographs. The research team probed about perceptions regarding how and why that particular antecedent, represented by the photograph, influences handwashing behavior. Results After coming out of the bathroom and dirt (moyla) on hands were the two antecedents that ranked highest. In all the categories, intervention-related antecedents (three key times for handwashing which included handwashing after coming out of the bathroom, after cleaning a child's anus and before food preparation; intervention provided items that included handwashing station, soapy water bottle, handwashing reminders from posters and community health provider visits) that were being promoted actively in this community were perceived favorably in the qualitative responses, but did not consistently rank higher than non-intervention items. However, many other antecedents were reported to influence when and where people wash their hands: cutting greasy fish, starting a meal, contact with oil and fat stuck to dishes, oil and lice from hair, sweat, unwashed vegetables, reminders from son and daughter or observing others wash hands, and observing the sunset. Conclusions Beyond well-recognized antecedents related to fecal contact and dirt on hands, we identified a broader set of antecedents not reported in the literature. Adopting a handwashing promotional strategy to highlight existing antecedents that people themselves have identified as important can help inform the content of an intervention that is more relatable and effective in increasing handwashing practices.